A criança nativa digital no contexto de filmes publicitários - Dias, Ana Luísa Antunes [UNESP] (2015)
This research aims to identify how the digital native child appears or is represented in contemporary advertising. More specifically, we intend to verify the contexts in which the digital native children is presented in advertising films made for brasilian television and which aspects of hypermodernity are widespread in the messages and social representations of this generation of children, transmitted by advertising. Digital Native (Prensky, 1999) is the name to the generation of children born from the twenty-first century that use digital technology with ease. Are children that living in hypermodernity, a term used by Lipovetsky and Charles (2004) to designate the contemporary society that is characterized by growing and unceasing evolution of these technologies and the intense speed of information flow and communication. By Bardin (2001) Content Analysis we analyzed nine (9) commercials films of brazilian television between 2009 and 2015, featuring children up to about 12 years interacting with or without electronic devices. With support from the Theory of Social Representations and relying on models of child representation, identified by Sampaio (2000); Meurer, (2002); Osaki (2003) and Orlandi (2012) in the national media that regularly employs stereotypes to represent children, envisioned the possibility of defining a new stereotype or model of child representation on the digital native children, to contribute to the research field about the psychic formation of children nowadays